Some Physico-Chemical Factors of Water of Al-Husainia Creek, Karbala Province, Iraq - Al-Saadi, A. A. J. J.; Mhaisen, F. T.; Hasan, H. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study of important physico-chemical factors of water of Al-Husainia creek during the period of May 2005 till the end of April 2006 indicated that water temperature showed clear monthly fluctuations ranged from 10 CÂ° during January to 33 CÂ° during August. Dissolved oxygen values ranged from 5.5 mg/ml during August to 14.8 mg/ml during January. Slight monthly changes were noticed in pH values, ranged from 7.7 during May to 9 during January. Also, slight monthly changes were recorded in salinity values which ranged from 0.67 ppt during October to 0.91 ppt during May. Clear fluctuation occurred in turbidity values which ranged from 12 cm during April to 177 cm during January. From the above results, it is clear that Al-Husainia creek water is suitable for fish life there.